Valores de referencia de actividad colinesterasica sanguínea en población laboral activa no expuesta a plaguicidas inhibidores de colinesterasa (2000)
ABSTRACT: The extended use of pesticides using cholinesterase inhibitors as their active principle, demands the determination of reference values in order to be able to monitor the levels of spill over into humans and for the take of rational clinical and epidemiological decisions. Such values are lacking in Colombia and this is the rationale for this work. The design of this study included two representative samples of labor active populations affiliated to the Social Health Care System and residing in the Aburrá Valley or in the east of the state of Antioquia. Six different techniques were used to measure cholinesterase levels. This report presents the results by using the Lovibond technique which uses whole blood. 827 individuals of both sexes and within an age range between 18 and 75 years were analyzed. 415 of them in Location 1 and 412 in Location 2. Only for the age group under 50 years was it possible to gather the number of people demanded by the statistical design. There was not significant variation between our results and those reported by the producers of Lovibond kit. Ours data are in agreement with the results of Henao et al in working children in Antioquia.